2004
DOI: 10.1007/s11249-004-8098-5
|View full text |Cite
|
Sign up to set email alerts
|

Microtribological Properties of Two-Phase Al2O3 Ceramic Studied by AFM and FFM in Air of Different Relative Humidity

Abstract: Commercially available, monolithic alumina ceramic was modified using CO 2 -laser irradiation by surface remelting and adding HfO 2 powder. Scanning electron microscopy revealed that the microstructure of the modified ceramic consisted of a fine lamellar eutectic Al 2 O 3 -HfO 2 phase embedded in the Al 2 O 3 matrix. Differences in the microtribological properties of the matrix and the eutectic phase could be measured by friction force microscopy (FFM) during unlubricated sliding contact with a silicon tip at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Experimental tests performed at variable humidity conditions by means of AFM reported μ values of 0.2 for Al 2 O 3 at 20%RH and values as high as 0.6 at 70%RH. 179 Interestingly, the authors also report that μ values remain constant when F v values ranging from 250 to 900 nN are applied at humidity levels below 50% but that they decrease in a hyperbolic fashion for high F v values at high humidity tests.…”
Section: Sio 2 and Al 2 O 3 Surfacesmentioning
confidence: 94%
“…Experimental tests performed at variable humidity conditions by means of AFM reported μ values of 0.2 for Al 2 O 3 at 20%RH and values as high as 0.6 at 70%RH. 179 Interestingly, the authors also report that μ values remain constant when F v values ranging from 250 to 900 nN are applied at humidity levels below 50% but that they decrease in a hyperbolic fashion for high F v values at high humidity tests.…”
Section: Sio 2 and Al 2 O 3 Surfacesmentioning
confidence: 94%
“…Higher feed rates led to a finer microstructure and thermally induced cracking was reduced by statistically supported selection of the process parameters. Further studies showed that by using precoating and injection processes as well as a suitable selection of powder additives in CO 2 -laser-assisted surface modification it was also possible to improve the tribological performance in lubricated (Ref 21,22) and in unlubricated systems (Ref 13,(23)(24)(25)(26)(27)(28) as well as under cavitation loading (Ref 29,30).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in recent studies that laser surface modification by remelting or embedding of second phases can result in reduced friction coefficient and wear rate of oxide ceramics [9][10][11][12]. Microtribological studies using AFM and FFM (atomic and friction force microscopy) showed a distinct difference in friction coefficient on the second phases and the matrix and hence the possibility for changing the friction behaviour by microstructural design [13].…”
Section: Introductionmentioning
confidence: 99%